Профессор Жовдак Валерий Алексеевич – к 70-летию со дня рождения - Ларин, Алексей Александрович; Морачковский, Олег Константинович; Трубаев, Александр Иванович (НТУ "ХПІ", 2016)
Статья посвящена 70-летию со дня рождения профессора В. А. Жовдака (9.03.1946 – 26.03.2009). Приведены краткие биографические сведения. Выделены основные результаты научной работы, которые позволили создать одно из важных направлений исследований на кафедре динамики и прочности машин НТУ "ХПИ", связанного с разработкой методов анализа случайных колебаний, оценки надежности и прогнозирования ресурса механических систем. Представлен список некоторых важных публикаций В. А. Жовдака.

The article is devoted to the 70th birthday of Professor Valery Zhovdak (9.03.46 – 26.03.2009). It presents a brief biographical information. The paper describes some his basic scientific results, which forms the foundation of one of the most important research area developed in the department of dynamics and strength of machines of National Technical University "Kharkiv Polytechnic Institute". It deals with the development of the methods for random vibration analysis, reliability assessment and a prediction of mechanical systems lifetime. A short list of some important scientific publications of professor Zhovdak is cited.
Professor Valery Zhovdak – 70th anniversary
Keywords: биографический очерк; надежность; прогнозирование ресурса; статистическая динамика; случайные колебания; кафедра динамики и прочности машин; НТУ "ХПИ"; biographical essay; reliability; service life prediction; statistical dynamics; random vibration